2016
DOI: 10.1016/j.jconrel.2016.07.024
|View full text |Cite
|
Sign up to set email alerts
|

A pH-sensitive stearoyl-PEG-poly(methacryloyl sulfadimethoxine)-decorated liposome system for protein delivery: An application for bladder cancer treatment

Abstract: Stealth pH-responsive liposomes for the delivery of therapeutic proteins to the bladder epithelium were prepared using methoxy-poly(ethylene glycol)5kDa-1,2-distearoyl-sn-glycero-3-phosphoethanolamine (mPEG5kDa-DSPE) and stearoyl-poly(ethylene glycol)-poly(methacryloyl sulfadimethoxine) copolymer (stearoyl-PEG-polySDM), which possesses an apparent pKa of 7.2. Liposomes of 0.2:0.6:100, 0.5:1.5:100 and 1:3:100 mPEG5kDa-DSPE/stearoyl-PEG-polySDM/(soybean phosphatidylcholine+cholesterol) molar ratios were loaded w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 63 publications
1
47
0
Order By: Relevance
“…[8][9][10][11] To control drug release profiles, external stimuli-sensitive properties such as temperature, pH, magnetic field and light have been applied for nanocarriers. [12][13][14][15][16][17][18][19][20][21] ThermoDox is one example of a temperature-responsive liposome designed to achieve drug release at tumor tissues under local heating of tumor tissues. [22][23][24] Temperature-sensitive polymer-modified liposomes are another platform to develop temperature-responsive liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] To control drug release profiles, external stimuli-sensitive properties such as temperature, pH, magnetic field and light have been applied for nanocarriers. [12][13][14][15][16][17][18][19][20][21] ThermoDox is one example of a temperature-responsive liposome designed to achieve drug release at tumor tissues under local heating of tumor tissues. [22][23][24] Temperature-sensitive polymer-modified liposomes are another platform to develop temperature-responsive liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, the protein TRAIL was encapsulated in the outer shell. [97] Results revealed that the BSA-loaded liposomes were colloidally stable at neural pH but showed remarkably high adhesion with MB49 cells and more effective administration to mice via bladder instillation under acidic environment. In vitro and in vivo experiment demonstrated that this multifunctional codelivery gel-liposome system showed significant inhibition of the tumor growth in the MDA-MB-231 xenograft tumor animal model.…”
Section: Liposomesmentioning
confidence: 99%
“…[94] Herein, the Dox was first encapsulated into CPP (R8H3) modified liposome. [91,97,98] For instance, Opanasopit and co-workers synthesized methylated N-(4-N,N-dimethylaminobenzyl) CS, which is water soluble at physiological pH. In the meantime, the protein TRAIL was encapsulated in the outer shell.…”
Section: Liposomesmentioning
confidence: 99%
“…They demonstrated that the liposomes which carried negative charges at physiological condition underwent a rapid size increase and aggregation at pH 6.5 due to the decreased zeta potential. Cytofluorimetric analysis and confocal microscopy results showed that at pH 6.5, fluorescein isothiocyanate‐labelled‐BSA (FITC‐BSA) loaded and N‐(Lissamine Rhodamine B sulfonyl)‐1, 2‐dihexadecanoyl‐sn‐glycero‐3‐phosphoethanolamine triethylammonium salt (rhodamine‐DHPE) labeled liposomes more efficiently associated with MB49 mouse bladder cancer cells and macrophages cells than at pH 7.4 . Yung et al.…”
Section: Nanocarriersmentioning
confidence: 99%